The Mediating Role of Individual Perception between Individual Orientation and Intention towards Sustainable Entrepreneurship - Koe, Wei-Loon; Ismail, Shafinar; Halim Mahphoth, Mohd; Abu Karim , Rizuwan (KnE Social Sciences, 2020)
The negative effects of entrepreneurial activities on the environment should not be disregarded. Sustainable entrepreneurship has been recognized as a strategy in rectifying environmental issues through entrepreneurial activities. However, developing sustainable entrepreneurs is still in its infancy stage in Malaysia. Most of Malaysia’s small and medium enterprises (SMEs) still regard it as a new practice and not many of them have actually embarked on it. As such, this study investigated the formation process of intention towards sustainable entrepreneurship through individual orientation and individual perception. This study surveyed 404 SMEs owner-managers in Malaysia through self-administered questionnaires. The results indicated that individual orientation positively and significantly related to intention towards sustainable entrepreneurship. Meanwhile, the results also showed a significant partially mediating the role of individual perception between individual orientation and intention towards sustainable entrepreneurship. This study contributed to the literature by confirming that the formation process of intention towards sustainable entrepreneurship was successfully influenced by two important determinants, namely individual orientation, and individual perception. Practically, it highlighted some crucial factors in promoting sustainable entrepreneurship among SMEs in Malaysia. Keywords: Entrepreneurship, intention, orientation, small and medium enterprises (SMEs), sustainability